2010
DOI: 10.1097/sla.0b013e3181ffc256
|View full text |Cite
|
Sign up to set email alerts
|

Machine Perfusion Versus Cold Storage for the Preservation of Kidneys Donated After Cardiac Death

Abstract: Hypothermic machine perfusion was associated with a reduced risk of DGF and better early graft function up to 1 month after transplantation. Routine preservation of DCD kidneys by hypothermic machine perfusion is therefore advisable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
216
5
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 281 publications
(253 citation statements)
references
References 30 publications
6
216
5
2
Order By: Relevance
“…23 It also notably improves outcomes by decreasing the prevalence of delayed graft function. 24,25 Because prolonged cold ischemic time (up to 48 hours) is widely accepted, en bloc kidneys procured from donor newborns can be transported easily to specialized centers willing to transplant these small organs. Thus, implementation of NICU DCDD programs nationwide could feasibly provide donor kidneys for selected transplant centers even if local or regional programs elect not to transplant kidneys from infant donors.…”
Section: Discussionmentioning
confidence: 99%
“…23 It also notably improves outcomes by decreasing the prevalence of delayed graft function. 24,25 Because prolonged cold ischemic time (up to 48 hours) is widely accepted, en bloc kidneys procured from donor newborns can be transported easily to specialized centers willing to transplant these small organs. Thus, implementation of NICU DCDD programs nationwide could feasibly provide donor kidneys for selected transplant centers even if local or regional programs elect not to transplant kidneys from infant donors.…”
Section: Discussionmentioning
confidence: 99%
“…But 1-year graft and patient survival was similar in both groups. 14 In contrast to the aforesaid study, Watson and associates found that there was no difference in the incidence of DGF preserved by machine perfusion or cold storage in kidney transplants from DCD. 15 The presence of DGF is an early surrogate marker of organ quality and preservation.…”
Section: Discussionmentioning
confidence: 68%
“…In a sub-analysis of 82 pairs of DCD kidneys from the European trial, the DGF rate in the HMP group was 53.7% compared to 69.5% in kidneys that were statically stored [85]. However, there was no significant difference in graft survival at 1 or 3 years.…”
Section: Hypothermic Machine Perfusionmentioning
confidence: 99%